2013
DOI: 10.1371/journal.pone.0083679
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Untreated Psychosis Is Associated with Temporal and Occipitotemporal Gray Matter Volume Decrease in Treatment Naïve Schizophrenia

Abstract: BackgroundLong duration of untreated psychosis (DUP) is associated with poor treatment outcome. Whether or not DUP is related to brain gray matter volume abnormalities in antipsychotic medication treatment naïve schizophrenia remains unclear at this time.MethodsPatients with treatment-naïve schizophrenia and healthy controls went through brain scan using high resolution Magnetic Resonance Imaging. DUP was evaluated using the Nottingham Onset Schedule (NOS), and dichotomized as short DUP (≤ 26 weeks) or long DU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…Delays in receiving treatment have been associated with poor outcomes. For instance, lengthy delays in untreated psychosis can predict poorer neurocognitive ability (Amminger et al, 2002;Gaynor et al, 2009), lower quality of life (Harrigan et al, 2003), impaired social functioning (Barnes et al, 2008), longer length of first hospitalisation (Penttila et al, 2013) and are associated with neuro-anatomical changes such as decreases in brain grey matter volume (Guo et al, 2013;Malla et al, 2011). Duration of untreated illness is also associated with worse outcomes in affective disorders (Dell'Osso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Delays in receiving treatment have been associated with poor outcomes. For instance, lengthy delays in untreated psychosis can predict poorer neurocognitive ability (Amminger et al, 2002;Gaynor et al, 2009), lower quality of life (Harrigan et al, 2003), impaired social functioning (Barnes et al, 2008), longer length of first hospitalisation (Penttila et al, 2013) and are associated with neuro-anatomical changes such as decreases in brain grey matter volume (Guo et al, 2013;Malla et al, 2011). Duration of untreated illness is also associated with worse outcomes in affective disorders (Dell'Osso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies have indicated that the exposure to antipsychotic medications may cause both structural (Jacobsen et al, 1998) and functional (Bluhm et al, 2007;Liang et al, 2006;Zhou et al, 2007a) changes in the brain. In addition, several previous studies have shown an inverse correlation between duration of untreated psychosis and reduced gray matter volume in schizophrenia patients (Crespo-Facorro et al, 2007;Guo et al, 2013). Thus, compared to chronic or medicated patients, drug-naive, first-episode schizophrenia patients have a unique value to be used to explore the neuropathological process of illness, and thus minimize the effects of potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…These results might suggest that AL model could also account for the neuroprogressive changes observed in schizophrenia (DeLisi, 2008). The neuroprogressive conceptualization of schizophrenia is supported by morphologic brain lesions positively correlating with duration of untreated psychosis (Guo et al, 2013;Malla et al, 2011;Penttila et al, 2010), total illness duration (Burke et al, 2008) and the number of psychotic episodes (Seok Jeong et al, 2005;van Haren et al, 2007). Furthermore, it has been found that symptomatic remission and functional recovery negatively correlate with the number of symptomatic exacerbations suggesting the cumulative systemic toxicity of AL throughout psychotic episodes (Marchesi et al, 2013).…”
Section: Allostatic Load Throughout the Lifespanmentioning
confidence: 89%